Evaluation of the Tourism Management CHSE Protocol during the Covid 19 Pandemic in the Situ Gunung Gede Pangrango National Park Area - Ismeth Emier Osman; Nurbaeti; Adam Rachmatullah; Fetty Asmaniaty; Jatna Supriatna; Djoni Wibowo (Institut Pertanian Bogor (IPB University), 2023)
This study aimed to evaluate the Tourism Management CHSE Protocol during the Covid 19 Pandemic in the Situ Gunung Gede Pangrango National Park Area. The framework of the approach used in this research was phenomenology, which was then enriched with the data collection techniques of study documentation, observation, and close-ended questionnaire. The analytical method utilized was the One Score One Indicator Scoring System, an analysis model that was used through developing elaboration of questionnaires in collecting data and evaluating various variables that researchers had determined. Then, two critical issues were examined in the polarization analysis to understand the differentiation between actors, namely polarization of direction and rating scale, and then tested statistically using Kruskal Wallis test to know the polarization significance. Overall, based on the assessment of 189 CHSE indicators, the data shows that the implementation of CHSE in Situ Gunung GGPNP results in a reasonable conclusion or score of 6. When viewed based on stakeholder polarization where the data shows there is no polarization of direction between stakeholders on CHSE management at Situ Gunung. Things are different when viewed in terms of average values, where the study results show the polarization of each actor's attitude scale on the CHSE implementation assessment. The aggressive strategy is carried out by optimizing three crucial aspects: 1) Strengthening CHSE Management Policies and Implementation; 2) Optimizing Ecotourism Carrying Capacity.